Selected African Countries : IMF Technical Assistance Evaluation; Public Expenditure Management Reform. (IMF Staff Country Reports; Country Report, 2006)
This report focuses on IMF Technical Assistance Evaluation-Public Expenditure Management (PEM) Reform in Selected African Countries. Most of the countries examined were colonies of the United Kingdom, inheriting similar and relatively simple budget systems based on an interpretation of the 'Westminster model' around the time of independence. Country reviews suggest that PEM problems are widespread and that there are few areas in the PEM systems of the countries covered that do not require strengthening in some way.